PROFESIONALITAS CREW DALAM MEMPERTAHANKAN RATING PROGRAM SI BOLANG TRANSâ”‚7 - Nurwati HH, Vita Herlinawati, Bedjo Sukarno & (Transformasi, 2016)
Professionalism crew includes two factors that is the impact from in and encouragement fromthe outside felt by all crew can increase working spirit and work crew. Crew who feelcomfortable with work done will make professionalism crew and growing his handiwork so thatit can be had an impact on the produce the program as a whole. With increasing produce alsoaffected with work performance and maintain rating program. The kind of in and motivationfrom out of professionalism crew resulted in which impressions message belongs to be toldcommunicator to communicant to realize motive connection. In this research that refers to theirprofessionalism crew factor that is applied to the program Si Bolang Trans7. One theory usedresearchers is as revealed by Tjokrowinoto (1996: 191) â€œ Their professionalism is the ability toplan, coordinates, and carry out its function in an efficient way, innovative, flexible, and havetheir work high ethicâ€. The research is the kind of research descriptive kualitatif by using themethod data collection of interview, observation, and documentation. This study attempts todescribing and analyze professionalism crew in maintaining rating the Si Bolang Trans7program. Interview this was done in Producer, Camera person, Reporter, and Editor programthe Si Bolang Trans7. The research result show that professionalism crew from the urge from theand encouragement from outside formed very good for crews in the program the Si BolangTrans7. This can be seen from the achievement of various indicators which is in encouragementfrom within. And there are also from the urge from outside. Professionalism crew was formedaffect business crew in reaching a the purpose of the program. And most importantly for all crewkeep professionalism in giving impressions to the spectators and get achievement program alsodefended a good rating.Keywords: professionalism, communication,production, television.